KONTRIBUSI LEMBAGA PENDIDIKAN ISLAM DALAM MEMBINA KARAKTER SISWA DI MIS NURUL IKHWAN - Arlina; Khairunnisa; Rizki Nazlia; Dinda Valiza; Fatih Alwi Haya Lubis (STAI Ihyaul Ulum Gresik, 2025)
Abstract: The purpose of this study is to determine how Islamic educational institutions influence MIS Nurul Ikhwan students' character development. A phenomenological approach is taken in the qualitative method's application. Techniques for gathering data include documentation, interviews, and observation. Data analysis was done using the reduction, presentation, and conclusion processes. The study's findings demonstrate how MIS Nurul Ikhwan helps students develop their moral character through regular infaq exercises, teachers' kind interactions, the provision of sound guidance and role models, and the application of sanctions that are commensurate with the severity of infractions. Keywords: Integrity, Islamic Education, and Character.